The Design of 50 GHz Gallium Arsenide Electro-Optic Modulator Arrays for Satellite Communications Systems - Walker, Robert Graham; Zhou, Yi (Frontiers in Physics, 2021)
Considerations are presented for the design of GaAs traveling-wave electro-optic modulator arrays for space data-link applications. Central to the modulator design is a low loss folded optical configuration giving direct, straight-line radio frequency (RF) access at one end of the device, with all fiber-optical ports at the opposite end. This configuration is a critical enabler for the close-packed monolithic modulator arrays needed for multi-channel applications. It also leads to much more compact packaging, improved fiber handling and contributes to high modulation bandwidths with low ripple by eliminating directional change in the RF feed arrangements. Both single Mach-Zehnder (MZ) and monolithic dual-parallel (IQ) modulators have been assessed up to 70GHz, with bandwidths around 50GHz achieved with a low-frequency ON/OFF voltage swing (V of 4.6V (a voltage.length product of 8.3Vcm). The folded devices can be significantly more compact than conventional ‘straight in-line’ modulators, while a modest array of devices (e.g. x4) can be accommodated in a package of similar dimensions to a single modulator. Design considerations for monolithic arrays of independently addressed MZ modulators (each with its own input fiber) are discussed and practical configurations proposed.